Comparing the Effect of Ice Massage and Acupressure on the Intensity of the Venipuncture Pain in Hemodialysis Patients - SHAHRIAR SAKHAEI,; HOSSEIN MOTAAREfI,; HASSAN EBRAHIMPOUR SADAGHEYANI, (International Journal of Pharma and Bio Sciences, 2018)
Pain as a distressing and unpleasant mental experience is one of the most important challenges of nursing. In hemodialysis patients undergoing 320 annual venipuncture, the pain caused by thick venous needles along the fistula often presents patients with anxiety and severe stress. Hence, in order to feel comfortable and relaxed, use off prophylactic methods of relieving pain for the patients is essential. Objective: This study was conducted to determine the effect of ice massage and acupressure at Hugo point on the severity of the venipuncture pain in patients undergoing hemodialysis. Methodology: In this clinical trial, 59hemodialysis patients with inclusion criteria of the study were selected through targeted sampling and were divided randomly into three groups: ice massage, acupressure, and control group. The tool used for collecting data was a questionnaire for social and personal information and Numerical Rating Scale [NRS] of 0 to 10. The data were analyzed using Statistical Package for the Social Sciences [SPSSVersion-16.0], chi-square, Fisher's exact test, Pearson correlation coefficient and one-way Analysis of Variance [ANOVA].The study result showed that There was no significant difference between the three groups regarding demographic variables (p> 0.05).The mean difference of pain severity caused by needle insertion in venipuncture was between the ice massage and acupressure (0.9), acupressure and control (1.0), ice massage and control (1.9) groups (p<0.05). Hence the study proved that use of acupressure, especially in combination with a cold, can be used as a safe and independent nursing method to reduce the pain of venipuncture in the fistula.